Disaster Risk Financing : Case Studies - Poundrik, Sandeep (2012)
In this note, the instruments supporting risk retention and risk financing at the national and regional/international levels will be the sole focus. Risk transfer, including insurance, is a very broad subject and requires a separate discussion; however, when a hybrid solution involves a transfer of risk or an instrument at the household or community level, a brief explanation of the instrument ensues. To this end, the note reviews examples generally considered to be good practices in the sector and seeks to elucidate well-regarded risk retention instruments and financing. The choice of instruments in disaster risk financing depends on many factors. One way of looking at it is to classify the disasters in terms of their expected severity and frequency. More frequent disasters with low expected severity are better financed by retaining the risk, as the cost of transferring such risk will be disproportionately high compared to the expected damages or payments. On the other hand, risk associated with low frequency-high severity disasters is best transferred to the international reinsurance market, as government may not have the capacity and resources to sustain the damages caused by such disasters. Finally, as the case studies in this note indicate, the uptake of risk retention and risk transfer mechanisms has made countries more resilient to natural disaster.